2001
DOI: 10.1021/bi002732+
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Import of Creb and AP-1 Transcription Factors Requires Importin-β1 and Ran but Is Independent of Importin-α

Abstract: Although the specific role of transcription factors (TFs) is nuclear, surprisingly little is known in quantitative terms regarding the pathways by which TFs localize in the nucleus. In this study, we use direct binding assays, native gel electrophoresis, and fluorescence polarization measurements to show for the first time that the cAMP-response element binding protein (CREB) and related AP-1 and jun and fos constituents are recognized by importin beta1 (Impbeta) with nanomolar affinity. We reconstitute the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 74 publications
0
81
1
Order By: Relevance
“…Similar to the cNLS, the HMG domain was recognized poorly by IMP␣ (K d ϭ 112 nM), although IMP␤ recognition was slightly increased in the presence of IMP␣ (K d ϭ 2.4 nM). Thus, SRY joins a less common but growing list of arginine-rich NLScontaining proteins recognized by IMP␤ rather than IMP␣ (14,22,29,(31)(32)(33) that include the Rev (RqaRRnRRRRwR) from HIV type 1 (32, 34), the Rex protein of human T cell leukemia virus type 1 (mpKtRRRpRRsqRKRppt) (33), and the AP-1 family transcription factor CREB (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the cNLS, the HMG domain was recognized poorly by IMP␣ (K d ϭ 112 nM), although IMP␤ recognition was slightly increased in the presence of IMP␣ (K d ϭ 2.4 nM). Thus, SRY joins a less common but growing list of arginine-rich NLScontaining proteins recognized by IMP␤ rather than IMP␣ (14,22,29,(31)(32)(33) that include the Rev (RqaRRnRRRRwR) from HIV type 1 (32, 34), the Rex protein of human T cell leukemia virus type 1 (mpKtRRRpRRsqRKRppt) (33), and the AP-1 family transcription factor CREB (26).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse IMP␣-GST and IMP␤-GST were expressed as described (24). Their functionality in terms of mediating nuclear import has been demonstrated (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear transport of c-Fos and c-Jun appears to be independent of importin ␣, because both proteins interact directly with the transport receptor importin ␤. The apparent affinities of the transcription factors for importin ␤, however, are rather low (13), and importin ␤-dependent transport has not been demonstrated in a permeabilized cell system so far.…”
mentioning
confidence: 95%
“…Some of these bind directly to the classic import receptor, importin ␤, without requiring any adapter protein. These include the proteins Rev and Rex of the human immunodeficiency virus (5,6) and the human T-cell leukemia virus (7), respectively, the T-cell protein tyrosine phosphatase (8), the parathyroid hormone-related protein (PTHrP) (9), cyclin B1 (10), the sterol regulatory element-binding protein 2 (SREBP-2 (11)), the zinc finger protein Snail (12), and the transcription factor CREB (13). Many of these proteins also contain basic NLSs.…”
mentioning
confidence: 99%
“…The cargo⅐importin-␣/-␤ complex is transported into the nucleus through the nuclear pore complex (NPC) (18,20). Several recent data have demonstrated that certain proteins are transported into the nucleus by importin-␣ alone (21), or by importin-␤ alone (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%